The Risk of Tuberculosis Infection in Non-dialysis Chronic Kidney Disease Patients - Li, Chia-Hsiang; Chen, Hung-Jen; Chen, Wei-Chun; Tu, Chih-Yen; Hsia, Te-Chun; Hsu, Wu-Huei; Chang, Chiz-Tzung; Huang, Chiu-Ching; Bau, Da-Tian; Chou, Che-Yi (Frontiers in Medicine, 2021)
Background: Patients with chronic kidney disease (CKD) receiving maintenance renal replacement therapy are at higher risk of tuberculosis (TB) infection. The risk of TB infection in CKD patients not receiving dialysis is unknown. Aim: We conduct this study to test the hypothesis that TB infection is negatively correlated to renal function. Design: Non-dialysis CKD stage 1–5 patients, admitted in China Medical University Hospital from January of 2003 to May of 2014, were enrolled in this study and were prospectively followed up to the diagnosis of TB, death, loss to follow-up, or December 2014. The risk factors of TB infection were analyzed using competing-risks regression analysis with time-varying covariates. The initiation of dialysis and patients' death were considered as competing events. Patients' estimated glomerular filtration rate (eGFR) and body mass index (BMI) were recorded at enrollment. Results: They were followed-up for a median duration of 1.4 years. Of the 7221 patients, TB infection was identified in 114 patients. Higher eGFR was associated with lower risk of TB infection (P < 0.01). The adjusted subdistribution hazard ratio (aSHR) was 0.82 [95% confidence interval (CI), 0.72 to 0.94] for every 5 ml/min/1.73 m2 increase in eGFR. In addition, higher BMI (p = 0.01) was associated with a lower risk of TB infection and the aSHR was 0.91 (95% CI, 0.85 to 0.98) for every 1 kg/m2 increase in BMI. Conclusion: Renal function and body mass index are independently associated with the risk of tuberculosis infection in patients with chronic kidney disease not receiving dialysis.